Effectiveness of a Marungko-Based Reading Approach in Primary Grades as Perceived by the Teachers at San Fernando District - Bona, Julie Pearl (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the implementation and perceived effectiveness of the Marungko-Based Reading Approach in the primary grades of selected public elementary schools in San Fernando District, Masbate Province. Anchored on Phonics Theory, Constructivist Learning Theory, and Sociocultural Theory of Learning, the study examined how teachers perceived the approach in terms of learner motivation, active participation, letter-sound mastery, and reading confidence. A descriptive-quantitative research design was used, with 30 public elementary teachers selected through convenience sampling. Data were gathered using a structured and validated questionnaire and analyzed through frequency count, percentage, weighted mean, and One-Way Analysis of Variance. Results showed that most respondents were female, married, bachelor’s degree holders, had 6–10 years of teaching experience, and had attended 6–10 trainings related to reading instruction. Teachers strongly agreed that the Marungko-Based Reading Approach was effective in enhancing learner motivation, letter-sound mastery, active participation, and reading confidence. The highest perception result was recorded for learner motivation, while reading confidence obtained the lowest but still favorable rating. Teachers also strongly agreed that they encountered implementation challenges, particularly limited training, time constraints, poor learner attendance, minimal parental support, difficulty sustaining learner attention, and lack of adequate instructional resources. The ANOVA result showed a significant difference in teachers’ perceptions when grouped according to demographic profiles. The study concludes that the Marungko-Based Reading Approach is a valuable foundational reading intervention, but its implementation requires stronger teacher training, instructional materials, parental involvement, and differentiated support. The study aligns with SDG 4, SDG 10, and SDG 17 by supporting quality education, reducing literacy gaps, and encouraging stakeholder collaboration. Its sustainability impact lies in strengthening educational, institutional, community, and socio-economic development through improved early literacy instruction.
Keywords: Active Participation; Early Literacy; Learner Motivation; Letter-Sound Mastery; Marungko-Based Reading Approach,; Primary Grades; Reading Confidence; Reading Instruction; Teacher Perception